2015
DOI: 10.1097/mpg.0000000000000750
|View full text |Cite
|
Sign up to set email alerts
|

Early Postnatal Growth in a Subset of Convalescing Extremely‐Low‐Birth‐Weight Neonates

Abstract: In a selected subset of noncritically ill, convalescing extremely-low-birth-weight neonates, after a brief period of unavoidable postnatal weight loss and body water adjustment, adequate nutrition from birth can enable a more homeostatic pattern of growth that approximates growth of the index fetus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 33 publications
2
5
0
3
Order By: Relevance
“…This resulted in failure of most infants to attain a weight above the 10th centile at 36 weeks on both the Fenton Growth Chart and Intergrowth 21st Project Postnatal Chart. Findings by Dejhalla et al among 21 ELBW infants with an uncomplicated hospital stay showed much better outcomes with 71% of infants having a weight above the 10th centile on discharge [25]. The study excluded infants with blood culture proven sepsis, necrotizing enterocolitis and neonatal surgery among other complications.…”
Section: Discussionmentioning
confidence: 99%
“…This resulted in failure of most infants to attain a weight above the 10th centile at 36 weeks on both the Fenton Growth Chart and Intergrowth 21st Project Postnatal Chart. Findings by Dejhalla et al among 21 ELBW infants with an uncomplicated hospital stay showed much better outcomes with 71% of infants having a weight above the 10th centile on discharge [25]. The study excluded infants with blood culture proven sepsis, necrotizing enterocolitis and neonatal surgery among other complications.…”
Section: Discussionmentioning
confidence: 99%
“…A TH enteral máxima administrada aos participantes não diferiu (p=0,07), assim como sua principal intercorrência esperada, NEC (p=0,70). Dejhalla 22 apresenta resultados semelhantes de incidência de NEC (10%) nos participantes submetidos à dieta hiperproteica. Há divergência com a literatura 23,24 em relação ao citado, já que o excesso de TH administrada, em especial pela via enteral, predispõe à NEC.…”
Section: Discussionunclassified
“…Durante o tempo de internação hospitalar não houve aceleração de velocidade de crescimento, mas sim desaceleração, apontando que o CEUR é uma regra aos RNMBP, assim como suas consequências futuras. 2,5,9,25 Van der Schoor 26 encontrou que o balanço do aminoácido lisina era significativamente aumentado nos prematuros em dieta enteral plena e Dejhalla 22 conclui que a taxa de crescimento em seu estudo foi mais acentuada durante o período de dieta enteral exclusiva. Tal desaceleração menos acentuada é indicativa de possível prevenção de CEUR nos participantes expostos ao maior aporte proteico enteral durante internação hospitalar, apesar da pequena diferença de infusão proteica entre os grupos (1,0g/kg/dia).…”
Section: Discussionunclassified
See 1 more Smart Citation
“…The goal for premature infants is to obtain a similar rate of growth and nutrient intake compared to a fetus of the same gestational age in utero [22][23][24]. It is often difficult for these premature infants to obtain adequate growth, since their intestinal function is less mature than their term counterparts [17].…”
Section: Probiotic Use In Premature Infantsmentioning
confidence: 99%